2020
DOI: 10.21037/atm.2019.12.102
|View full text |Cite
|
Sign up to set email alerts
|

Web-based study on Chinese dermatologists’ attitudes towards artificial intelligence

Abstract: Background: Artificial intelligence (AI) has become a powerful tool and is attracting more attention in the field of medicine. There are a number of AI studies focusing on skin diseases, and there are many AI products that have been applied in dermatology. However, the attitudes of dermatologists, specifically those from China, towards AI, is not clear as few, if any studies have focused on this issue.Methods: A web-based questionnaire was designed by experts from the Chinese Skin Image Database (CSID) and pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 30 publications
2
20
0
1
Order By: Relevance
“…The third-place, surprisingly, is about unemployment with 467 responses or 46%. In this regard, this study converges with the academic literature on the perception of AI integration at work in that people are not very concerned about being replaced by AI but more concerned about human-AI interaction (Pinto dos Santos et al, 2019;Sarwar et al, 2019;Shen et al, 2020;Sit et al, 2020). Table 3 shows 52% of the respondents hold a negative view of the AI managers, and 51% rated themselves below average regarding AI knowledge.…”
supporting
confidence: 77%
See 1 more Smart Citation
“…The third-place, surprisingly, is about unemployment with 467 responses or 46%. In this regard, this study converges with the academic literature on the perception of AI integration at work in that people are not very concerned about being replaced by AI but more concerned about human-AI interaction (Pinto dos Santos et al, 2019;Sarwar et al, 2019;Shen et al, 2020;Sit et al, 2020). Table 3 shows 52% of the respondents hold a negative view of the AI managers, and 51% rated themselves below average regarding AI knowledge.…”
supporting
confidence: 77%
“…Similarly, Pinto dos Santos et al (2019) surveyed 263 medical students and found although most respondents thought AI could revolutionize (77%) and improve radiology (86%), 83% did not think human physicians would be replaced. Likewise, Shen et al (2020) found nearly 96% conducts 1,228 Chinese dermatologists from 30 provinces and regions in a webbased survey that believed AI roles are to assist with diagnosis and treatment. On the other hand, while a survey of 484 responses of 19 UK universities medical students show that a majority of students (88%) will play an important role in healthcare yet, nearly half the respondents express their concern about job loss in radiology due to AI (Sit et al, 2020).…”
Section: Students' and Professional's Attitude Toward Aimentioning
confidence: 99%
“…The survey results showed that almost Chinese dermatologists considered the role of AI in “assisting dermatologists in their daily diagnosis and treatment activities.” AI should be implemented in secondary hospitals and skin tumors in the future. [ 22 ] Our results show that even on the premise that the diagnostic accuracy of Youzhi AI software was reduced, there was no significant difference between its accuracy and the average level of dermatologists, and Youzhi AI software was even better than dermatologists in recognizing the type of skin tumor diagnosed by dermoscopic images. Moreover, the diagnostic accuracy of dermatologists with primary dermoscopic diagnostic ability was not as good as that of Youzhi AI software.…”
Section: Discussionmentioning
confidence: 84%
“…An overwhelming majority of Chinese dermatologists are favorably disposed to AI and think the role of AI will be in “assisting the daily diagnosis and treatment activities for dermatologists” [ 94 ].…”
Section: Methodsmentioning
confidence: 99%